PENGARUH PENGGUNAAN MODEL PEMBELAJARAN BENAR SALAH BERANTAI TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS VIII SMP NEGERI 1 PEKANBARU - Indah Apritasari; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research is based on the low motivation of learning PPKn Grade VIII students in SMP Negeri 1 Pekanbaru. Symptoms shown by student quickly get bored in PPKn lesson assignments from 37% student, only 8 people who diligently deliver assignment on time. Only 27% of student in the class are interested ini studying PPKn, only active students are certain student, and that’s it, from the number of student in the class only 30% of student actively ask and give opinions. Student pay less attention to the material delivered because they feel bored with monotonous learning methods which are more dominated by teachers, so studnts, become less activeThat the formulation of the problem in this reseach is